2000
DOI: 10.1002/1521-4141(200010)30:10<2871::aid-immu2871>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Altered major histocompatibility complex class II peptide loading in H2-O-deficient mice

Abstract: The biosynthesis of MHC class II/peptide complexes involves classical, cell surface MHC products as well as the intracellular component H2‐M, required for the removal of invariant chain‐derived CLIP and for peptide loading. The function of another intracellular class II heterodimer, H2‐O, is the matter of some controversy. The physical association of H2‐O with H2‐M and co‐localization in class II+ vesicles suggest a related function in peptide exchange. Furthermore, the distinctive thymic distribution of H2‐O … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
44
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 37 publications
8
44
3
Order By: Relevance
“…DR1-biotin CLIP complexes were formed by incubation of 500 nM DR1 with 5 M biotin-CLIP for 18 h at 37°C. For dissociation, preformed complexes were diluted 10-fold and incubated in 20-l volumes with 100 M unlabeled MAT (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). After neutralization, the complexes were captured on L243-coated microtiter wells at 4°C and biotin complexes were measured with streptavidin-europium as previously described (5).…”
Section: Peptide Dissociation Assayssupporting
confidence: 90%
See 2 more Smart Citations
“…DR1-biotin CLIP complexes were formed by incubation of 500 nM DR1 with 5 M biotin-CLIP for 18 h at 37°C. For dissociation, preformed complexes were diluted 10-fold and incubated in 20-l volumes with 100 M unlabeled MAT (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). After neutralization, the complexes were captured on L243-coated microtiter wells at 4°C and biotin complexes were measured with streptavidin-europium as previously described (5).…”
Section: Peptide Dissociation Assayssupporting
confidence: 90%
“…Unilamellar liposomes containing purified DR1 and/or DM were generated as described in Materials and Methods. Samples containing identical quantities of DM and DR1 distributed together or separately into liposomes were incubated for 3 h at pH 5 with 1 M biotin-MAT (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) peptide. After chilling on ice, liposomes were solubilized in 1% NP40 and biotin-MAT-DR1 complexes were quantified by europium fluorescence immunoassay (f).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…H2-O −/− B cells outcompeted WT B cells by ∼2-to 5-fold, but did not completely take over the GC niche. This suggests that H2-O-dependent modulation of Ag presentation may be subtle, which is supported by previous studies that examined presentation on the cellular level and found varying effects of H2-O depending on the specific epitope examined (9,(11)(12)(13)(14)(15)25). Nevertheless, small differences in Ag presentation, especially when considering a complex Ag mix containing many individual epitopes, could have a considerable impact on the immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, mass spectrometry analysis of peptide repertoires has demonstrated that HLA-DM/H-2M functions as a "peptide editor", displacing not only CLIP peptides but poorly-fitting endogenous peptides [104]. A related molecule, HLA-DO/H-2O, serves a similar function [105,106], although its specificity is distinct. Thus, mass spectrometry has played a central role in uncovering the existence of molecules that fine-tune the peptide repertoire displayed by class II MHC molecules.…”
Section: Involvement Of Hla-dm/h-2m In Antigen Presentation By Class mentioning
confidence: 99%